Psychometric Properties of the EFL Learning Plateau Inventory for Medical Students - Mehdi Mirzaei (Journal of Medical Education Development, 2020)
This study was designed to examine the factor structure and psychometric properties of the English as a Foreign Language Learning Plateau Inventory (FLLPI) for medical students. English as a Foreign Language (EFL) plateau refers to the cessation of progress in language learning in intermediate and upper-intermediate level. A total of 210 medical students whose English level was rated as intermediate and upper-intermediate through the administration of Oxford Placement test (OPT) responded to the FLLPI. Confirmatory Factor Analysis was performed using Structural Equation Modeling (SEM). The reliability of the measurement instrument was calculated by Cronbach's alpha (0.978). The findings of the first-order factor analysis confirmed the adequacy of the ten-factor model for the FLLP. Moreover, the second-order confirmatory factor analysis showed that all 10 factors have a sufficient factor load to predict the factors influencing EFL plateau. Also, the goodness of the model fit revealed the following results which demonstrate that the model enjoyed a high fitness: CMIN / DF= 1.961 RMSEA= 0.61, GFI= 0.945, AGFI= 0.968, CFI= 997/0, NFI= 0.949, TLI= 0.978, IFI= 0.926 and RFI= 965.0. The results not only support the FLLPI's multidimensionality, but also indicate the usefulness of the FLLPI in EFL plateau research among medical students whose English level are rated as intermediate and upper-intermediate.